Regional identities and cultural contact in the literatures of post-conquest England - Dolmans, E (2016)
This thesis explores the geographic complexity of English identity in the High Middle Ages by examining texts that reflect moments and spaces of cultural contact. While interaction with a cultural Other is often thought to reinforce national identity, I challenge this notion, positing instead that, in the texts analysed here, cultural meetings prompt the formation or consolidation of regional identities. These identities are often simultaneously local and cross-cultural, inclusive but based in community ties and a shared sense of place. Each of the four chapters examines a different kind of regional identity and its relation to Englishness through romances and historiographical texts in Anglo-Latin, Anglo-Norman, and Middle English. Discussion primarily focuses on the Gesta Herwardi, Gaimar's Estoire des Engleis, Fouke le Fitz Waryn, Gui de Warewic, Boeve de Haumtone, Le roman de toute chevalerie, and Richard Coer de Lyon. Each of these texts negotiates English identity in relation to a cultural Other, and balances various aspects of cultural identity and scales of geographic affiliation. While some focus exclusively on a particular locality, others create inclusive regional identities, draw together the foreign and the familiar, or depict England as a region on the edge of an interconnected world. These texts show that Englishness can carry different meanings, nuances, and identitary strategies that depend on context, location, or ideology. Together, they forge an image of England that is diverse and multinucleated. Its borders become spaces of meeting, connection, and cultural overlap, as well as division. These works establish a strong English identity while articulating England’s necessary relationship with other places, spaces, and peoples, challenging not the borders of England, but the borders of Englishness.